Determination of the coefficient sliding friction value in the contact the cutting tool-composite - Khavin, G. L.; Hou, Zhiwen (Національний технічний університет "Харківський політехнічний інститут", 2022)
One of the most important characteristics in calculating the cutting tool wear in contact with the processed composite is the friction coefficient. In most calculations, including the finite element method, the friction coefficient is traditionally set as a constant, the value of which is often taken from experience without any reason. However, when machining reinforced composites, there are too many mechanical and technological factors that have a very strong effect on the friction coefficient value. This influence is associated not only with the initial heterogeneity of the composite, but also with the constant actual change in the contact conditions over time, caused by the wear of the tool cutting part. The friction coefficient value in real conditions of contact interaction has a very complex physical content due to the presence of products of fibers and binder destruction in the contact, partial a binder melting at a temperature in contact, and the unevenness of the cut fibers presence. This article presents a formulation that allows you to calculate the value of the friction coefficient depending on the volumetric content and the inclination angle of the reinforcing elements. It is proposed to calculate the friction coefficient value as the product of two factors, one of which is responsible for the filler volumetric content, and the other for the reinforcing elements orientation. The calculations use the mixtures theory relations. The presented expressions for calculations are based on the use of limited experimental information presented by various authors. The available data are often contradictory and relate, as a rule, to predicting the processed surface quality of unidirectional glass and carbon fiber reinforced plastics. At the same time, the friction coefficient value in the calculations has a significant impact on the representation of tool wear and life. The model does not take into account the contact pressure effect, mutual sliding velocity and temperature on the friction coefficient value, which will be the subject of further research in this direction.

Однією з найважливіших характеристик при розрахунку зносу ріжучого інструменту при контактній взаємодії при обробці композиту, є коефіцієнт тертя. У більшості розрахунків, у тому числі і методом скінчених елементів, коефіцієнт тертя зазвичай задається як постійна величина, значення якої часто приймається з досвіду без жодної підстави. Однак при механічній обробці армованих композитів є дуже багато факторів механічного і технологічного характеру, які дуже сильно впливають на величину коефіцієнта тертя. Цей вплив пов'язаний не лише з початковою неоднорідністю композиту, а й постійною фактичною зміною умов контакту у часі, що викликано зносом різальної частини інструмента. Значення величини коефіцієнта тертя в реальних умовах контактної взаємодії має дуже складний фізичний вміст через присутність в контакті продуктів руйнування волокон і сполучного, часткового розплавлення сполучного при температурі контакту, присутності нерівномірно зрізаних волокон. У цій статті представлено формулювання, що дозволяє розраховувати величину коефіцієнта тертя в залежності від об'ємного вмісту та кута нахилу елементів армування. Запропоновано розраховувати значення коефіцієнта тертя як добуток двох співмножників, один з яких відповідає за об'ємний вміст наповнювача, а інший за орієнтацію елементів армування. У розрахунках застосовуються співвідношення теорії сумішей. Подані вирази для розрахунків базуються на використанні обмеженої експериментальної інформації, представленої різними авторами. Наявні дані часто мають суперечливий характер і стосуються, як правило, прогнозування якості обробленої поверхні односпрямованих скло- та вуглепластиків. У той же час величина коефіцієнта тертя в розрахунках значно впливає на уявлення зношування і стійкості інструменту. Модель не враховує вплив на величину коефіцієнта тертя контактного тиску, швидкості взаємного ковзання і температури, що буде предметом подальших досліджень у цьому напрямку.
Визначення величини коефіцієнту тертя ковзання в контакті ріжучий інструмент-композит
Keywords: friction coefficient; abrasive wear; filler content; reinforcement direction; tool wear; коефіцієнт тертя; абразивний знос; вміст наповнювача; напрямок армування; зношування інструменту